THE EFFECT OF THE HEAD OF THE MANAGEMENT FUNCTION ON WORKLOAD AND THE APPLICATION OF NURSE CARING ATTITUDE WITH NURSE CHARACTERISTICS AS INTERVENING VARIABLES IN INSTALLATION OF INPATIENT X HOSPITAL IN JAKARTA - Deasy Sugesty, Kemala Rita, Idrus Jus'at (Yayasan Pendidikan Medika Indonesia, 2024)
The quality of health services in quality hospitals is influenced by the quality of physical facilities, types of available personnel, drugs and medical devices, and the service delivery process. The kind of staff member who has an important role in realizing the quality of service in the hospital is the nurse, who must demonstrate the ability to provide the best service. The hallmark of nursing services that become the spirit of the nursing profession is caring, and several factors can influence this. Therefore, the purpose of this study is to analyze the managerial function of the head of the ward in terms of the workload and caring of the implementing nurse with the characteristics of nurses as intervening variables in the ward hospital X Jakarta. The research method used is quantitative cross-sectional with questionnaire data collection techniques, observations and interviews. The results showed that there was an influence of the managerial function of the head of the ward on the characteristics of nurses, the caring attitude of nurses and there was an influence of the characteristics of nurses on the caring attitude of nurses and the effect of workload on the caring attitude of the implementing nurses in the inpatient installation of RS X Jakarta and there was no influence of the managerial function of the head of the room and the characteristics of the implementing nurse on the workload of the implementing nurse in the inpatient installation of RS X Jakarta.